A new subtype of autosomal dominant diabetes attributable to a mutation in the gene for sulfonylurea receptor 1. - Huopio, H; Otonkoski, T; Vauhkonen, I; Reimann, F; Ashcroft, F; Laakso, M (2003)
BACKGROUND: ATP-sensitive potassium (KATP) channels are major regulators of glucose-induced insulin secretion in pancreatic beta cells. We have described a dominant heterozygous mutation--E1506K--in the sulfonylurea receptor 1 (SUR1) gene (ABCC8) in a Finnish family, which leads to congenital hyperinsulinaemia due to reduction of K(ATP)-channel activity. We aimed to characterise glucose metabolism in adults heterozygous for the E1506K mutation. METHODS: Glucose tolerance was assessed by an oral glucose tolerance test, insulin secretion by the intravenous glucose tolerance test and hyperglycaemic clamp, and insulin sensitivity by hyperinsulinaemic euglycaemic clamp in 11 people heterozygous for the E1506K mutation and 19 controls. FINDINGS: Four people who were heterozygous for the SUR1 E1506K mutation had diabetes, five had impaired glucose tolerance, one had impaired fasting glucose, and one had normal glucose tolerance. Although glucose-induced, first-phase insulin secretion was normal in children younger than 10 years of age who were heterozygous for the SUR1 E1506K mutation (n=2; 66 and 334 pmol/L), it fell rapidly after puberty (n=3; 12-32 pmol/L), and was almost completely lost in adulthood (n=11; 12-32 pmol/L). Furthermore, these heterozygous people had a substantial reduction in maximum glucose-stimulated insulin secretion during hyperglycemic clamp (carriers without diabetes 422 pmol/L; carriers with diabetes 97 pmol/L). By contrast, insulin sensitivity (M/I value) was normal in carriers of the E1506K mutation who did not have diabetes and was reduced by 15% in those who were heterozygous with diabetes (0.07 in those without diabetes and 0.05 in those with the disorder; not significantly different from controls). INTERPRETATION: Heterozygous E1506K substitution in the SUR1 gene causes congenital hyperinsulinism in infancy, loss of insulin secretory capacity in early adulthood, and diabetes in middle-age. This variant represents a new subtype of autosomal dominant diabetes.